2002
DOI: 10.1016/s0029-7844(01)01672-6
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant high dose rate vaginal brachytherapy as treatment of stage I and II endometrial carcinoma

Abstract: Adjuvant high dose rate vaginal brachytherapy in thoroughly staged patients with intermediate-risk endometrial carcinoma provides excellent overall and disease-free survival with less toxicity and at less cost compared with whole-pelvic radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 12 publications
0
39
0
3
Order By: Relevance
“…Pelvic and para-aortic lymph node invasion were 11.4% and 5.3% respectively in our data. By the way of higher rates of pelvic and para-aortic lymph node invasion; lyphadenectomy seems valuable for endometrial cancer surgery (14,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic and para-aortic lymph node invasion were 11.4% and 5.3% respectively in our data. By the way of higher rates of pelvic and para-aortic lymph node invasion; lyphadenectomy seems valuable for endometrial cancer surgery (14,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of favorable clinical outcomes persists, especially an improved survival rate and a quicker treatment recovery time when using single‐channel VC HDR BT 2 , 4 , 5 , 6 , 7 . In particular, a simulation study by Barney et al (3) evaluating rectal and bladder toxicity using a single‐channel VC HDR BT reported that less than 5% of the patients (1 out of 24) developed a Grade 3 or higher toxicity level.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly because the ICRU reference point is relative in position only to the VC applicator, which is chosen to fit tightly within the vaginal canal so to eliminate air gaps, (4) while the closest rectal point depends solely on the anatomical position of the rectum, and mostly varies between two patients even in VCs with a same diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"sampling", liegt zum einen in der Tatsache, daß lediglich eine verminderte Aussage über den Nodalstatus gemacht werden kann, zum anderen sind bis zu 39% aller Lymphknotenmetastasen <2mm, so daß ein Befall nur in 10-31% makroskopisch verifiziert werden kann (Hirahatake et al, 1997). (Pfleiderer, 1991;Poulsen et al, 1997;Horowitz et al, 2002;Larson et al, 1998 Gesamtüberleben war jedoch statistisch nicht signifikant (Roberts et al, 1998). (Ball et al, 1996;Pfleiderer, 1991;Sutton et al, 1994).…”
Section: Anhand Dieser Prognosefaktoren Ist Es Möglich Die Indikatiounclassified